Facies and Environmental Analysis of Aqra Formation in Southern Aqra Anticline North Iraq - Amaar J. Al-Taiiy (Tikrit Journal of Pure Science, 2023)
The successions of Aqra Formation in north Iraq are composed of alternative Limestone,dolomitic limestone and limestone rich sets macrofossils rudist,benthonic foraminifera,coral and successive arrival bitumen and calcareous. From petrography study, divided formation rocks to six microfacies: Rudist lime boundstone microfacies (A1), Bioclasts rudist lime grainstone microfacies (A2), Miliolids foraminiferal lime grainstone microfacies (A3), Loftusia foraminiferal lime packstone microfacies (A4), Algal lime packstone microfacies (A5),Bioclastic- echinoderms lime wackestone microfacies (A6). Many diagenetic processes have been recognized such as: Cementation, dissolution, dolomatization. The facies Aqra Formation deposition in environments back reef,reef and fore reef.